A Randomized Controlled Trial of an Optimized Smoking Treatment Delivered in Primary Care. Issue 10 (14th February 2018) - Piper, Megan E; Cook, Jessica W; Schlam, Tanya R; Jorenby, Douglas E; Smith, Stevens S; Collins, Linda M; Mermelstein, Robin; Fraser, David; Fiore, Michael C; Baker, Timothy B
Abstract: Background: The effectiveness of smoking cessation treatment is limited in real-world use, perhaps because we have not selected the components of such treatments optimally nor have treatments typically been developed for and evaluated in real-world clinical settings. Purpose: To validate an optimized smoking cessation treatment package that comprises intervention components identified as effective in factorial screening experiments conducted as per the Multiphase Optimization Strategy (MOST). Methods: Adult smokers motivated to quit were recruited from primary care clinics ( N = 623). Participants were randomized to receive either recommended usual care (R-UC; 10 min of in-person counseling, 8 weeks of nicotine patch, and referral to quitline services) or abstinence-optimized treatment (A-OT; 3 weeks of prequit mini-lozenges, 26 weeks of nicotine patch + mini-lozenges, three in-person and eight phone counseling sessions, and 7–11 automated calls to prompt medication use). The key outcomes were self-reported and biochemically confirmed (carbon monoxide, CO <6 ppm) 7-day point-prevalence abstinence. Results: A-OT participants had significantly higher self-reported abstinence rates than R-UC participants at 4, 8, 16, and 26 weeks (ORs: 1.91–3.05; p <. 001). The biochemically confirmed 26-week abstinence rates were lower than the self-reported 26-week rates, but revealed a similar treatment effect size (OR = 2.94, p < .001). There was no moderation of treatment effects on 26-week abstinence by demographic, psychiatric, or nicotine dependence variables. A-OT had an incremental cost-effectiveness ratio for 26-week CO-confirmed abstinence of 7, 800. Conclusions: A smoking cessation treatment that is optimized via MOST development meaningfully enhances cessation rates beyond R-UC smoking treatment in smokers seen in primary care. Clinical Trial Registration: NCT02301403. Abstract : A smoking cessation intervention engineered using a new methodology helped significantly more smokers in primary care successfully quit smoking than did typical clinical smoking cessation treatment.